How Financial Factors Shape the Capital Structure of Manufacturing Companies in the Basic Chemical Industry - Santi Octaviani; Kodriyah Kodriyah; Nikke Yusnita Mahardini; Zalfa Kaila Widi Utami (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the influence of financial factors on the capital structure of basic chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample selection method used is purposive sampling, with specific criteria resulting in a sample of 51 companies and a total of 255 data points. After data processing, 80 outliers were identified, reducing the final sample to 175 company data points. This research adopts a quantitative approach, utilizing multiple linear regression analysis with SPSS version 25. The findings reveal that profitability, asset structure, company size, and business risk have a significant impact on capital structure. In contrast, sales growth and dividend policy do not show a significant contribution to capital structure. Based on these findings, it is recommended that companies in the basic chemical manufacturing sector focus on improving profitability, optimizing asset structure, and managing business risks effectively to strengthen their capital structure. Additionally, company size should be considered when making financing decisions. Since sales growth and dividend policy were not significant factors, firms might prioritize internal financial management and risk control over aggressive sales expansion or dividend adjustments when aiming to optimize their capital structure. Future research could explore other potential factors or use alternative methodologies to deepen understanding in this area.